The Effect Of H2O2 On The Bleaching-Scouring Simultaneous Process Of 100% Cotton Fabric With Pad - Batch System - Luciana Luciana; Agni Salamah (Universitas Insan Cendekia Mandiri, 2023)
Simultaneous processes are processes that are implemented simultaneously where the process and substances used do not interfere with each other, the purpose of each process of preparation for refinement is implemented to remove starch on the warp threads in the form of natural impurities, external impurities and natural pigments in a short time and satisfactory result. The purpose of this research is to improve the quality of the results of the scouring process, and bleaching simultaneously in the pad-batch system. This research method was carried out by varying the concentration of H2O2: 20 g/l, 30 ml/l and 40 g/l using a 70% squeeze effect and a batching time of 12 hours. After the experiments were carried out, tests were implemented on starch content, absorption capacity - capillary test, degree of whiteness, tear strength test by tongue method and aging test (ΔE). From the experimental and test results, the optimum conditions showed that the higher the concentration of H2O2 up to a concentration of 40g/l with the same batching time for 12 hours was obtained at a concentration of H2O2 of 30 g/l where in these conditions starch could be removed from the material properly. Absorption power in 1 minute absorbs color as high as 4 cm. The white degree test results are 61.66%. The tear strength in the warp direction was 9.675 N and the tear strength in the weft direction was 7.475 N and the (ΔE) color difference value of L* (Lightness) or the brightness level was 73.74 for light colors; medium color 62.68; and dark color 20.49